2009
DOI: 10.3928/08910162-20091019-01
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Thai Workers’ Use of Hearing Protection

Abstract: This study used an ecological model to examine Thai workers' beliefs and attitudes toward using occupational hearing protection. Data collection involved focus group sessions with 28 noise-exposed workers at four factories in Chiang Mai Province and an interview with a safety officer at each organization. Detailed content analysis resulted in the identification of three types of factors influencing the use of hearing protection: intrapersonal, including preventing impaired hearing, noise annoyance, personal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Exposure to noise in industrial settings is known to annoy workers, [19] and evidence suggests that workers who accept noise as part of everyday work are less likely to be annoyed by noise. [20] In addition, noise can also cause annoyance indirectly by interfering with performance and communication as well as impairing hearing [21] However, workers' perceived susceptibility to NIHL and the perceived severity of NIHL varies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to noise in industrial settings is known to annoy workers, [19] and evidence suggests that workers who accept noise as part of everyday work are less likely to be annoyed by noise. [20] In addition, noise can also cause annoyance indirectly by interfering with performance and communication as well as impairing hearing [21] However, workers' perceived susceptibility to NIHL and the perceived severity of NIHL varies.…”
Section: Discussionmentioning
confidence: 99%
“…This supports findings of other studies that have used ecological models to explain hearing protection behavior amongst workers. [19,30] An important consideration for an ecological model is the community level. There were suggestions in this study that workers did not care about noise and enjoyed loud sounds outside of work, suggesting a community culture of not thinking of noise as a hazard.…”
Section: Discussionmentioning
confidence: 99%
“…The model has also been used to guide development and evaluation of public health interventions (Bishop & Glanz, 2010). In occupational health, ecological models have been used to examine factors relating to use of hearing protection (Tantranont et al., 2009), participation in workplace health promotion programs (Plotnikoff, Prodaniuk, Fein, & Milton, 2005), to examine occupational stress among firefighters (Salazar & Beaton, 2000), and to develop disaster management plans (Beaton et al., 2008).…”
Section: Background Of Modelmentioning
confidence: 99%
“…1,2 However, an increase in the prevalence of NIHL was reported in various countries [3][4][5][6] and in Thailand. The percentage of Thai workers who reported NIHL 7 increased from 1.2% in 2000 to 4.7% in 2001. When NIHL was classified by job category, it was found that the incidence in staff personnel at Songklanagarind Hospital 8 was 28.1% and in stone milling workers 9 the incidence was 30.0%, whereas dentistry personnel and a control group showed no significant difference.…”
Section: Introductionmentioning
confidence: 97%